EDUKASI BERKELOMPOK UNTUK PENINGKATAN KEPATUHAN TERAPI PADA ODHIV DI WILAYAH KERJA PUSKESMAS RAWASARI KOTA JAMBI - Kusdiyah, Erny; Darmawan, Armaidi; Aurora, Wahyu Indah Dewi; Harahap, Huntari; Syauqy, Ahmad; Nuriyah, Nuriyah (Medical Dedication (medic) : Jurnal Pengabdian kepada Masyarakat FKIK UNJA, 2024)
HIV/AIDS infection (ODHIV) remains a significant public health issue in Indonesia. One of the main challenges in managing HIV/AIDS is adherence to antiretroviral (ARV) therapy among ODHIV. Low adherence can lead to drug resistance, decreased quality of life, and increased risk of virus transmission. Factors influencing ARV adherence include stigma, discrimination, and the knowledge of ODHIV about the therapy. Education was conducted through group counseling, starting with a pre-test to assess participants' knowledge about HIV treatment. After the pre-test, a counseling session on "The Importance of ARV Adherence for People Living with HIV" was held, concluding with a post-test. A total of 27 participants took part in this activity, with the majority being male (59%) and the largest age group being 20-30 years (41%). Pre-test results indicated that 44% of participants had a low initial understanding. However, post-test results showed a significant improvement; 37% of participants scored in the 71-80 range, and another 37% scored in the 81-90 range. These results indicate that the education provided successfully enhanced participants' understanding of the importance of ARV adherence. Despite the improvements, challenges remain regarding adherence, particularly for those lacking family support. This highlights the need for additional strategies to enhance social support for ODHIV. Participation in this activity was predominantly male, with most participants having a high school education. The post-test results confirmed a significant increase in understanding compared to the pre-test. Puskesmas and community health workers should conduct regular monitoring and evaluation of ARV adherence to prevent loss to follow-up in treatment.